2022
DOI: 10.1039/d1fo03825g
|View full text |Cite
|
Sign up to set email alerts
|

Pre-diagnosis meat intake and cooking method and ovarian cancer survival: results from the Ovarian Cancer Follow-Up Study (OOPS)

Abstract: The relationships between pre-diagnosis meat intake and ovarian cancer survival were limited and controversial. To date, no study has taken account of cooking methods. Thus, we aimed to firstly clarify these associations based on the Ovarian Cancer Follow-Up Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…Nonetheless, these aforementioned factors are difficult to modify. Diet, a potentially modifiable aspect, has an impact on the prognosis of OC, which has been confirmed by numerous epidemiologic studies [ 9 , 10 , 11 ] and our research [ 12 , 13 , 14 ]. Clear evidence also indicated that pre-diagnosis high diet quality contributed to improving OC survival [ 9 ].…”
Section: Introductionsupporting
confidence: 84%
“…Nonetheless, these aforementioned factors are difficult to modify. Diet, a potentially modifiable aspect, has an impact on the prognosis of OC, which has been confirmed by numerous epidemiologic studies [ 9 , 10 , 11 ] and our research [ 12 , 13 , 14 ]. Clear evidence also indicated that pre-diagnosis high diet quality contributed to improving OC survival [ 9 ].…”
Section: Introductionsupporting
confidence: 84%
“…Thus, it is particularly crucial to find modifiable prognostic factors that can improve the prognosis of OC. Of note, diet is a modifiable factor that could contribute to the improvement of OC survival, which has been verified by our previous research ( 8 10 ).…”
Section: Introductionsupporting
confidence: 84%
“…Pre-diagnosis dietary information was measured at baseline through the FFQ, its validity and reliability have been verified by previous studies ( 8 , 9 ). The reproducibility coefficients (Spearman correlation coefficients and intraclass correlation coefficients) were above 0.5 for most food groups, and the correlation coefficients (Spearman correlation coefficients) were between 0.3 and 0.7 for most food groups between the FFQ and weighed dietary records ( 8 10 ). All newly diagnosed OC patients were required to report their usual intake frequency of each food item during the year prior to OC diagnosis, with seven response options: almost never, 2–3 times per month, 1 time per week, 2–3 times per week, 4–6 times per week, 1–2 times per day, and more than two times per day.…”
Section: Methodsmentioning
confidence: 85%
“…24,27 The previous studies confirmed the validity and reliability of the food frequency questionnaire. 26,29 The Spearman correlation coefficients and intraclass correlation coefficients for reproducibility were above 0.5 for most food groups, and the correlation coefficients between the FFQ and weighed dietary records also satisfied this condition (range: 0.3–0.7). All patients reported the frequencies of each food item consumed in the year before they were diagnosed with OC.…”
Section: Methodsmentioning
confidence: 66%
“…At the baseline, all eligible women provided information on demographics and lifestyle factors which included age, alcohol drinking status, education level, monthly average income, dietary change, smoking status, tea drinking status, and physical activity. 26,27 Among them, physical activity was calculated by metabolic equivalent tasks from the 2011 update of a major compendium of physical activities. 28 Dietary change was defined as participants who had deliberately changed their eating habits from one year before diagnosis and categorized as yes and no.…”
Section: Data Collectionmentioning
confidence: 99%